2011
DOI: 10.1007/s00726-011-1020-1
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies from patients with celiac disease inhibit transglutaminase 2 binding to heparin/heparan sulfate and interfere with intestinal epithelial cell adhesion

Abstract: Autoantibodies from patients with celiac disease (CD) can influence transglutaminase 2 (TG2) activity and its cellular functions, but the exact mechanisms have remained unknown. Our objective was to study whether autoantibodies could modulate TG2 binding to heparin/heparan sulfate (HS) and intestinal epithelial cell attachment to fibronectin-TG2 matrix. Anti-TG2 antibodies were purified by TG2 affinity chromatography from sera of patients with active CD. Serum and antibody effects on TG2 binding to heparin/HS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Some of the biological effects include (a) inhibition of cell adhesion and migration, most probably by modulating the heparin sulfate proteoglycan binding site [176] and by enhancing the expression of matrix metallo-proteases, (b) inhibition of epithelial cell differentiation by interfering with TG2 mediated TGF-b1 activation [177], (c) inhibition of several steps in angiogenesis [178], and (d) increasing the permeability of blood-brain barrier.…”
Section: Celiac Antibodies Targeting Conformational Epitopes On Tg2mentioning
confidence: 99%
“…Some of the biological effects include (a) inhibition of cell adhesion and migration, most probably by modulating the heparin sulfate proteoglycan binding site [176] and by enhancing the expression of matrix metallo-proteases, (b) inhibition of epithelial cell differentiation by interfering with TG2 mediated TGF-b1 activation [177], (c) inhibition of several steps in angiogenesis [178], and (d) increasing the permeability of blood-brain barrier.…”
Section: Celiac Antibodies Targeting Conformational Epitopes On Tg2mentioning
confidence: 99%
“…HS chains have also high affinity binding for TG2 Lortat-Jacob et al 2012) which is associated with the HS chains of syndecan-4 in a variety of cell types Lortat-Jacob et al 2012;Nadella et al 2015;Wang et al 2011Teesalu et al 2012). HS proteoglycans have a physiopathological role in the kidney and have also been suggested to modulate TG2 trafficking in the kidney ).…”
Section: Heparan Sulfate Proteoglycans and Tg2 Export In Ckdmentioning
confidence: 95%
“…Studies with the application of the HS blocking agent Surfen (Schuksz et al 2008) clearly showed reduced extracellular TG2 ), suggesting that if specific interference with TG2-syndecan 4 interactions could be achieved, then it would also serve as a therapeutic intervention site. Several HS binding sites within TG2 have been proposed (Lortat-Jacob et al 2012;Teesalu et al 2012). Our group have identified two distant basic amino acid clusters, RRWK (262-265) and KQKRK (598-602) which would come together to form a conformationally dependent high affinity binding site (Lortat-Jacob et al 2012).…”
Section: Tg2 As a Therapeutic Targetmentioning
confidence: 96%
“…In addition, TG2 antibodies derived from celiac patients have been demonstrated to induce proliferation of intestinal epithelial cells [160]. Further, celiac patient sera or purified anti-TG2 antibodies are able to reduce the attachment of epithelial cells to the TG2-fibronectin matrix [161]. Moreover, treatment of intestinal epithelial cells with sera from celiac patients has been reported to increase the transepithelial permeability of these cells [162].…”
Section: Biological Effects Of Anti-tg2 Antibodiesmentioning
confidence: 97%